A complex history of rearrangement in an orthologous region of the maize, sorghum, and rice genomes - Ilic, Katica (National Academy of Sciences, 2003)
The sequences of large insert clones containing genomic DNA that is orthologous to the maize adh1 region were obtained for sorghum, rice, and the adh1-homoeologous region of maize, a remnant of the tetraploid history of the Zea lineage. By using all four genomes, it was possible to describe the nature, timing, and lineages of most of the genic rearrangements that have differentiated this chromosome segment over the last 60 million years. The rice genome has been the most stable, sharing 11 orthologous genes with sorghum and exhibiting only one tandem duplication of a gene in this region. The lineage that gave rise to sorghum and maize acquired a two-gene insertion (containing the adh locus), whereas sorghum received two additional gene insertions after its divergence from a common ancestor with maize. The two homoeologous regions of maize have been particularly unstable, with complete or partial deletion of three genes from one segment and four genes from the other segment. As a result, the region now contains only one duplicated locus compared with the eight original loci that were present in each diploid progenitor. Deletion of these maize genes did not remove both copies of any locus. This study suggests that grass genomes are generally unstable in local genome organization and gene content, but that some lineages are much more unstable than others. Maize, probably because of its polyploid origin, has exhibited extensive gene loss so that it is now approaching a diploid state.